Regulation of flowering processes by some internal correlations in dwarf French bean - Debouck, Daniel G. (International Society for Horticultural Science, 1983)
For a proper characterization of beans, as well as for future improvements in basic yield potential, it is necessary to understand the process of node formation on stems and the evolution of the axils, either vegetative or floral, at these nodes. Within a pure nonphotoperiodic var. of Phaseolus vulgaris described as determinate, under controlled conditions, a natural though narrow variability appears in the no. of nodes on the main stem. Linked to this no., a clear morphological acropetal gradient to flowering is expressed by the central axillary branches. The vegetative activity of the main stem apex can be slightly extended by the very early removal of the primary leaves. This results in a longer vegetative structure before the main stem terminal raceme, and in a much more important vegetative structure on the central axillary branches. Reversions to vegetative organogenesis can be observed on the last ones. When this treatment is delayed, the mentioned effect disappears on the main stem; it is less marked on the central branches and concentrated at the upper axils. These results throw new light on the way to consider the differences in growth habit and yield potential. (AS)